1997
DOI: 10.1177/107769909707400313
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Up and Silencing Out in Face of a Changing Climate of Opinion

Abstract: This paper relies on panel data from Israel to test the spiral of silence the0 y ' s assumptions concerning overt expression of opinion. The research design provides a way to examine the effect of a changing climate of opinion on who speaks up and who silences out over time and changing circumstances. In addition, a multivariateapproach is adopted to test the role of climate perceptions relative to other factors, and extend our understanding of public speech. Perceptions of the climate of opinion are found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…And education is not always positively associated with willingness to argue. Shamir (1997), for example, also found that education was negatively associated with people's willingness to express opinion on a controversial issue to a stranger who disagrees with them in a long bus ride.…”
Section: Willingness To Argue Political Conversation and Majority Pmentioning
confidence: 90%
“…And education is not always positively associated with willingness to argue. Shamir (1997), for example, also found that education was negatively associated with people's willingness to express opinion on a controversial issue to a stranger who disagrees with them in a long bus ride.…”
Section: Willingness To Argue Political Conversation and Majority Pmentioning
confidence: 90%
“…Even so, there have been many suggestions about how to measure the opinion climate. Some have asked about the opinion among the general public (Shamir, 1997), while others have focused on different reference groups (Moy, Domke, & Stamm, 2001;Oshagan, 1996). An interesting and maybe also troublesome aspect in previous research is the lack of mass media indicators in many studies.…”
Section: The Spiral Of Silence: Theory and Previous Findingsmentioning
confidence: 99%
“…A few studies have used panel data. Shamir (1997) used a two-wave panel to investigate the spiral of silence and climate change, and McDonald, Glynn, Kim, and Ostman (2001) used a fourwave panel from 1948 and conducted a secondary analysis on opinion climate and candidate preference.…”
Section: The Spiral Of Silence: Theory and Previous Findingsmentioning
confidence: 99%
“…Even so, there have been many suggestions about how to measure the opinion climate. Some have asked about the opinion among the general public (Shamir, 1997), while others have focused on different reference groups (Moy, Domke, & Stamm, 2001;Oshagan, 1996). An interesting and maybe also troublesome aspect in previous research is the lack of mass media indicators in many studies.…”
Section: The Spiral Of Silence: Theory and Previous Findingsmentioning
confidence: 99%
“…A few studies have used panel data. Shamir (1997) used a two-wave panel to investigate the spiral of silence and climate change, and McDonald, Glynn, Kim, and Ostman (2001) used a fourwave panel from 1948 and conducted a secondary analysis on opinion climate and candidate preference.…”
Section: The Spiral Of Silence: Theory and Previous Findingsmentioning
confidence: 99%